The Sakhalin Ainu: origin and population contacts according to cranial-metric data - Moiseyev V.G.; Zubova A.V. (Вестник археологии, антропологии и этнографии)
The study is focused on recent population history of the Sakhalin Ainu people, which remains rebated over the last 70 years. Albeit it is generally accepted that the Sakhalin Ainu are decedents of Ainu migrants from Hokkaido, significant cranial differences has been revealed between these two related populations. Thus, while M. Levin argued in favor of the Nivkh component in the Sakhalin Ainu population, A. Kozintsev, based on the analysis of cranial non-metric characteristics, assumed the admixture of the Ainu with the Ulchi people, and we in our earlier studies assumed that the Sakhalin Ainu included the descendants of the Okhotsk culture people. The influence of interregional contacts between the Sakhalin Ainu and Kuril-Kamchatka populations has not been previously considered. We analyzed individual cranial metric data on the Sakhalin Ainu, the Hokkaido Ainu, and several ancient and historical samples from the Far East region using canonical variate analysis with subsequent clustering of the CVs scores with K-means algorithm. The results revealed high level of morphological diversity of the Sakhalin Ainu sample. The analysis supports that the Sakhalin Ainu are decedents of the Hokkaido Ainu migrants, which admixed with a number of populations of different origin. In addition to the previously assumed Nivkh, Ulch and ancient Okhotsk components in the Sakhalin Ainu, we assume a rather strong influence of the Itelmens, who, according to the results of our study, may be descendants of the population of the Old Bering Sea culture people.